Tall cell carcinoma with reversed polarity of breast cancer: a rare case report and review of the literature - Duan, Wenqi; Zhang, Longmei; Gao, Jinqi; Wang, Zhe; Ren, Mengjie; Wu, Huajian; Deng, Ya; Guo, Chunlong; Jiang, Jianing (Frontiers in Oncology, 2025)
Tall cell carcinoma with reversed polarity (TCCRP) is a primary invasive breast cancer that is clinicopathologically characterized by reversed polarity of the nucleus of the tumor cells near the cell edge. This pathologic feature is so rare that only 82 cases of TCCRP have been reported worldwide since it was first reported in 2003. Herein, we present the 83rd case of TCCRP. Going one step further than the previous reports, our case includes genetic testing. We sought to explore whether there are new mutation sites, with a view to identifying more therapeutic options for patients in future, to find PIK3CA p.H1047R mutation and IDH2 R172T mutation.We have found the macrophase makers CD68/CD163 double positive in this patient, which may indicate a poor prognosis in the early time. Therefore, the patient was treated with postoperative radiotherapy. The patient continues to be followed up for prognostic evaluation, and no recurrence or metastasis occurred until now. The case has represented a full view to gaining an improved understanding of TCCRP.